Developments in Legal Education: Beyond the Primary School Model - William Twining (Legal Education Review)
The late nineteen-eighties have been the occasion for a spate of birthday celebrations in law schools around the Commonwealth. This reflects the fact that the nineteen sixties saw an enormous expansion of legal education throughout the common law world, including the foundation of many new law schools, some of them the first in a given jurisdiction, country or region. The age of majority of a law school seems almost invariably to be set at either twenty or twenty-five years. Some institutions have marked their coming of age by publishing collections of essays that in different ways reflect on the past with pride or nostalgia or disillusion. Most view the future with apprehension, largely because of the economic crisis that faces higher education in nearly all countries in the English speaking world. Four recent publications exemplify the mood. The Faculty of Law of the University of Lagos, born in 1961, celebrated its anniversary with a collection of essays on Law and Development to mark the event. Dar-es-Salaam, born within weeks of Lagos, but hardly an identical twin, produced an imaginatively conceived collection of largely autobiographical essays poignantly entitled Limits of Legal Radicalism. Two other recent publications perform similar functions for legal scholarship: the now venerable Modern Law Review marked its fiftieth birthday with an illuminating survey of the state of legal scholarship in the common law world; this exhibits the wry acceptance of lowering of sights by an ageing radical. Finally a relative youngster, the University of Trento, has published an interesting symposium on Legal Scholarship in Africa which even more clearly that other documents many of the practical constraints, political, economic and social, under which contemporary legal researchers and scholars operate, especially in the Third World. In their different ways all of these publications combine reports of significant achievements with a sense of aspirations not really fulfilled and a quiet pessimism about the future about the future. In short, the mood of many institutions on their twenties seems to be one middle-aged acceptance of second best. Nearly all of these documents have quite understandably adopted the relatively parochial standpoint of academic lawyers in university or polytechnic law schools. The central concerns are with the familiar, but narrow, issues of curriculum, scholarly output and what might be called the ideology of legal education ... the much-rehearsed litany of differing approaches to academic law loosely labelled “blackletter” or “expository”, “trade school”, “socio-legal”, “contextual”, “law and development”, “clinical”, “skills”, “critical” and so on. In this paper I propose to adopt a broader perspective in two respects: I shall look at some general trends and issues in the Commonwealth, that vast and amorphous network of countries that are loosely linked together by a shared imperial past, by the common law, and perhaps most important in the long run, by the English language: I shall interpret legal education more broody to include not only specialized education and vocational training in university, polytechnic and independent professional training schools, but also a whole range of activities from law in schools to continuing education of the judiciary at all levels; from formation of paraprofessionals to the development and retraining of specialists; and the vast but relatively neglected subject of legal education for non-lawyers, which ranges far beyond mis-named “service” teaching of law for businessmen, accountants , social workers and the police to include activities aimed at raising the consciousness of and providing practical tools for grass-roots activists, trade unionists and ordinary citizens to help them to understand and use and cope with law as it affects them in their daily lives and work. In one respect, however, my focus will be narrow: legal education (or mis-education) is delivered and takes place in many arena and contexts besides specialized law schools. It occurs in law offices, government departments, plush hotels, schools, factories, villages and the home. It is delivered by non-lawyers and the media as well as by those who call themselves law teachers. However, I shall focus on specialized law schools as the actual or potential hub of any system of legal education. In the second part of the paper I phase law schools need to take more seriously than they have done in the past the idea that they should conceived, planned, financed, and equipped to become multipurpose centres that are concerned in a sustained way with all levels of legal education in society. This argument is not new. It was advanced in a report by the International Legal Center in 1975 entitled Legal Education in a Changing World5 with which Professor Yash Ghai and I were associated. That exercise was an education for me. Since then the world, legal professions, patterns of practice, legal education and some of my own views and perceptions have changed, but largely in ways that confirm and strengthen the main themes of that report. The argument is not intended to provide a blue-print for all law schools to follow; it is rather to suggest that perceptions, discussions and decisions within the higher reaches of legal education need to take account of some far-reaching trends and a wider agenda of issues than the traditionally inward-looking discourse of legal education has encompassed.